Effects of microcurrent therapy combined with High-Intensity Interval Training on the reduction of localized abdominal adiposity: a randomized clinical trial: Microcurrent in localized adiposity - Korelo, Raciele Ivandra Guarda; Pesaski, Aline; Santos, Nandara Lopes dos; Silva, Natalia de Paiva da; Anjos, Rubia Alana Souza dos; Macedo, Ana Carolina Brandt de; Gallo, Rubneide Barreto Silva; Vojciechowski, Audrin Said (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: The combination of aerobic exercise and transcutaneous microcurrent application (Microcurrent Electrical Stimulation - MES) was shown to have a positive effect on localized abdominal adiposity(LAA) reduction. However, the effect of the combination of MES and high-intensity interval training (HIIT) is still unknown. Objective: This study aimed to evaluate the effect combination of MES and HIIT on LAA reduction. Methods: 39 sedentary women with LAA, distributed in a Control Group (CG), an Exercise Group (EG), and a Microcurrent plus Exercise Group (MEG) participated in this randomized clinical trial. The CG was not submitted to intervention. The EG was submitted to a HIIT protocol (80% of Heart Rate max in a functional circuit) and MEG was submitted to abdominal transcutaneous application of MES prior to HIIT, 2x/week, during 5 weeks. The outcomes were collected by a blind evaluator and measured in three moments (before the 1st intervention, and after the 5th and 10th intervention), based on body composition parameters, anthropometric data, physical activity level (PAL), body satisfaction, quality of life (QoL), and lumbar functionality. Results: After 10 interventions, MEG showed significant improvement in skinfolds, QoL, and body satisfaction, but no significant difference compared to EG or CG. Regarding PAL, MEG differed significantly in relation to CG, but not in relation to EG. Conclusion: The combination of MES and HIIT in 10 interventions did not show satisfactory results for LAA reduction compared to HIIT, but the increase in PAL and the improvement in lumbar functionality may provide positive effects in the medium-term, although further studies are required.